Structure, Mechanical and Optical Properties of Silicon-Rich Al–Si–N Films Prepared by High Power Impulse Magnetron Sputtering; Coatings; Vol. 9, iss. 1 - Zenkin S. P. Sergey Petrovich; Konusov F. V. Fedor Valerievich; Lauk A. L. Aleksandr Lukyanovich; Zelentsov D. Yu. Denis Yurjevich; Demchenko S. G. Stanislav Gennadjevich (2019, 2019)
Title screen